Forecasting Electricity Consumption In Algeria Using Artificial Neural Networks - Chekouri, Sidi Mohammed; Sahed, Abdelkader (جامعة الوادي - University of Eloued, 2022)
This paper uses artificial neural network (ANN) method to forecast electricity consumption in Algeria. For this purpose, two independent variables which are GDP (Gross Domestic Product) per capita and population are used to forecast electricity consumption. The performance of the models is measured using R squared and the mean absolute percentage error (MAPE). The results reveal that the ANN model based on modeling electricity consumption as a function of economic indicators shows better performance than the ANN time input model. Also, results show that the projected electricity consumption in Algeria will reach 76.06 and 94.66 billion Kwh in years 2020 and 2025 respectively. Thus, A better electricity forecast is important for the policy makers when building future energy plants for the country.
مقال
Keywords: Electricity Consumption ; Forecasting ; Artificial Neural Networks ; Algeria